'We will think about it': Drama, curriculum and transformative learning in south-eastern Nigeria. Issue 2 (1st July 2015) - Nwadigwe, Charles E.; Nwadigwe, Francisca A.
The transformative role of drama, theatre and artistic education on the learning outcomes of children has been well established over time. However, while this subject and method of teaching and learning are being advocated and progressively embraced in many regions of the globe, the educational authorities in south-eastern Nigeria appear reluctant to adopt it. Hence the demand for the inclusion of drama as a separate subject in the foundational and basic school curricula remains a contentious issue. In the context of a new curriculum that now includes Cultural and Creative Arts as a subject in the primary and junior secondary schools, this study examines the existing policies on and the current practice of drama and theatre for learning in the sample area. It interrogates the key issues involved and points to a way forward for sustainable and transformative child education in south-eastern Nigeria.